Support for students with mental disorders a challenge for universities - Dobrychłop, Anna (Understanding Disability: Issues, Research, Reflections, 2021)
The situation of people with mental disorders is more difficult and more complex than the situation of people with other types of disability. Perceiving them, through the prism of negative stereotypes functioning in society describing the disease, as well as the mentally ill person itself, causes many, often irreversible consequences. Support for students with mental disorders but also those experiencing mental health crises is an important challenge faced by universities in Poland today. On the one hand, each university is required to adapt the form of education to the needs and capabilities of students with disabilities, on the other hand, the lack of specific procedures defining the type, form and principles of providing support in relation to the mentally ill, often does not allow for taking appropriate actions. This reality is not facilitated by the existence of many harmful stereotypes, and as a result social isolation from the mental ill.